A Proteomics Study of Hormone Induction of Defence Related Proteins in Kauri (Agathis australis) - Nayagar, Thilana (Auckland University of Technology, 2014)
Kauri (Agathis australis) is currently threatened by a pathogen, Phytophthora Taxon agathis (PTA) against which there are few effective treatments. Hormone induction may potentially induce the plant defence system and provide some resistance against the pathogen. The objective of this thesis was to determine if treatment with the hormones, methyl jasmonate (MJ) and ethylene (ethephon, ET) induces defence related proteins. A proteomics study was carried out to identify potential defence related proteins using SDS-PAGE and LC-MS. Numerous proteins were identified including common plant proteins such as RuBisCO as well as two potential defence related proteins, a super oxide dismutase and an acid phosphatase. This protein study was the first of its kind done in Kauri. Acid phosphatase was selected as a target for an enzyme induction kinetics study. Kauri plants were treated with the hormones MJ and ET alone and in combination. A spectrophotometric acid phosphatase assay was carried out to quantify enzyme concentration changes with time over a period of twelve days. The results of the enzyme assay showed a statistically significant increase in acid phosphatase activity when Kauri was treated with MJ alone and also when treated with a combination of MJ and ET. The treatment with MJ alone caused an induction of enzyme activity of 1.2 times higher than that of the control. The treatment with MJ and ET in combination caused an induction of enzyme activity 1.8 times higher when compared to the control. In conclusion, hormone treatment with MJ and ET has been shown to induce a plant defence related protein in Kauri which may have potential application in Phytophthora disease management. Further research will be required to determine if it is possible to prime Kauri defence related proteins by hormone treatment in order to confer PTA disease resistance.
Keywords: Kauri; Hormone induction